Africanos “livres” em Mato Grosso (1853 - 1864) : um estudo filológico, histórico e discursivo - Façanha, Juliana Lima (2019)
This thesis aims to present an interdisciplinary study of the corpus Livro de Registro da correspondência e mais acontecimentos relativos aos africanos livres entregues pelo Governo Imperial à Sociedade de Mineração da Província. 1853 – 1864, selected from the Public Archive of the State of Mato Grosso, stored on shelf 10, folder 383. Under Philology principles and its three functions - substantive, adjective and transcendent, we presented facsimile and, semi-diplomatic editions of the corpus. Based on paleographic studies, we analyzed the writing aspects in the corpus based on the guideline proposed by Cambraia (2005), prioritizing the following paleographic aspects: morphology, line, angle, size and the weight of the alphabetic characters; the vowel system; the consonant system (improper consonant clusters, twinned consonants, consonant substitutions); the diacritics; abbreviating signs and vocabular separation. For the socio-historical analysis, we mobilized the philology transcendent function and based on aspects of black men slavery trajectory in Brazil so as to better understand the historical aspects of the “Livro de Registro”. The socio-historical approach, based on our corpus, allowed us to reestablish important aspects in relation to the presence of free African people in the Province of Mato Grosso in the nineteenth century. Using Discourse Analysis concepts in their new theoretical-methodological approaches from Dominique Maingueneau’s proposals, we analyzed the enunciative scene of the corpus and the constitution of the discursive ethos, besides deepening in the interdisciplinary study between the Philology and the French Discourse Analysis guidance. This thesis is linked to the Research for the History of Brazilian Portuguese - Mato Grosso - PHPB-MT, offered by the Post-Graduation Program in Language Studies of the Federal University of Mato Grosso Language Institute, regarding the descriptive investigation of the Brazilian Portuguese based on corpora produced in the nineteenth century Mato Grosso, according to the PHPB national project – For a History of the Brazilian Portuguese.